Bilingual Test as a Test Accommodation to Determine the Mathematics Achievement of Mainstream Students With Limited English Proficiency - S. Kanageswari Suppiah Shanmugam; Ong Saw Lan (Malaysian Journal of Learning and Instruction, 2013)
Purpose â€“ This study aims to investigate the validity of using bilingual test to measure the mathematics achievement of students who have limited English proficiency (LEP). The bilingual test and the English-only test consist of 20 computation and 20 word problem multiple-choice questions (from TIMSS 2003 and 2007 released items. The bilingual test consists of items in Malay and English languages. The English teachers classified their students into LEP and non-LEP groups.